1995
DOI: 10.1161/01.cir.91.8.2120
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Gene Polymorphism Is Associated With Myocardial Infarction but Not With Development of Coronary Stenosis

Abstract: Segregation of the ACE I/D polymorphism is a pervasive genetic risk factor for MI in whites but has no evident effect on the events leading to stenosis of the coronary arteries. This suggests that risk of MI is influenced by two independent processes--atherogenesis that leads to coronary stenosis followed by conversion to MI. The renin-angiotensin system appears to confer significant risk of infarction by influencing the conversion to MI but has no apparent effect on the development of atherostenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
56
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(66 citation statements)
references
References 16 publications
9
56
1
Order By: Relevance
“…12 Since that time a lot of studies were performed in which ACE genotype was used as a tool, through association studies, to investigate the role of tissue ACE in human disease pathogenesis. [13][14][15][16][17] Taken together, the available evidence supports the notion that the DD ACE genotype adversely influences specific cardiovascular diseases but appears to do so in specific geographical areas and in particular patient subgroups. 18 This can be a possible explanation of the inconsistency of association between ACE genotype and ED.…”
Section: Introductionsupporting
confidence: 63%
“…12 Since that time a lot of studies were performed in which ACE genotype was used as a tool, through association studies, to investigate the role of tissue ACE in human disease pathogenesis. [13][14][15][16][17] Taken together, the available evidence supports the notion that the DD ACE genotype adversely influences specific cardiovascular diseases but appears to do so in specific geographical areas and in particular patient subgroups. 18 This can be a possible explanation of the inconsistency of association between ACE genotype and ED.…”
Section: Introductionsupporting
confidence: 63%
“…These results are contradictory to another report which demonstrated that the mutant deletion allele was associated with a low BMI. 24 On further comparison of the hypertensive overweight/obese and control groups in the current study, a significant difference was found between the frequency of the insertion/insertion genotype and between the allele frequencies of insertion and deletion alleles. While no significant association was found between the ACE insertion/deletion polymorphism and BMI in the hypertensives, a significant association was observed with hypertension.…”
Section: Discussionmentioning
confidence: 52%
“…Soluble ACE activity was measured by hydrolysis of a radiolabeled synthetic substrate, [glycine-1- 14 C]hippuryl-L-histidyl-L-leucine (3 mCi/mmol). 42 The presence of phenol red prevented the use of the fluorometric assay.…”
Section: Vascular Cell Phenotypesmentioning
confidence: 99%
“…Furthermore, cell and tissue ACE levels have also been shown to be modulated by ACE gene polymorphism in humans. 11,12 Since Cambien et al 13 first described a significant association between the I/D polymorphism and myocardial infarction, many studies have tried to examine the association of the ACE genotype, not only with ischemic heart disease 14 -17 but with a variety of conditions ranging from hypertension 18,19 to coronary artery restenosis, 14,20,21 cardiac hypertrophy, 16,22,23 pulmonary hypertension, 24 diabetes, 25 and nephropathy. 26 -28 The results of these studies are contradictory and stress the importance of experimental models for testing the impact of the ACE gene polymorphism and its associated modulation of ACE expression on the cardiovascular and renal responses to these pathological processes.…”
mentioning
confidence: 99%